Does the gender mix among employers influence who gets hired? A labor market experiment - Alexia Gaudeul; Ayu Okvitawanli; Marian Panganiban (Friedrich Schiller University Jena, 2015)
We consider in this paper whether the gender mix at the level of decision-makers in firms can influence gender representation at the employee level. We run a laboratory experiment whereby we present a pair of independent employers with applications from two potential employees. We consider whether the gender of the other employer will influence an employers hiring decision. We find that the gender mix among employers plays a role in the individual hiring decisions of female members. Female employers when paired with a male employer are more likely to choose a female applicant over an equally competent male applicant. Results of an Implicit Association Test (IAT) and answers to a post-experimental questionnaire show that explicit beliefs about relative gender performance are significantly associated with the observed hiring bias, while implicit attitudes do not appear to play a role.
Keywords: J71; J78; C91; 330; discrimination; employment; gender quotas; hiring; IAT; implicit attitudes; labor markets